UPAYA MENINGKATKAN MINAT DAN HASIL BELAJAR IPA MATERI PERAMBATAN BUNYI MELALUI ZAT PADAT DENGAN MEDIA TELEPON MAINAN PADA SISWA KELAS IV SDN SIGEMPOL 01 SEMESTER 1 TAHUN PELAJARAN 2021/2022 - Suhada, Abdilah Agus (JGuruku: Jurnal Penelitian Guru, 2023)
ABSTRAK Pembelajaran IPA siswa kelas IV SDN Siegempol 01 Brebes Kabupaten Brebes masih menggunakan metode ceramah, kurang terlibatnya siswa secara aktif selama proses pembelajaran dan siswa sulit mengaitkan konsep IPA dalam kehidupan sehari-hari.. Hal ini berakibat pada minat dan hasil belajar siswa yang rendah. Terlihat dari hasil ulangan harian IPA materi perambatan bunyi melalui zat padat yang sebagian siswa memperoleh nilai dibawah KKM yang telah ditentukan. Tindakan yang dilakukan untuk permasalahan tersebut adalah dengan penerapan percobaan alat peraga untuk memahami materi pembelajaran. Tujuannya untuk mengetahui dan mendeskripsikan minat dan hasil belajar siswa kelas IV SDN Sigempol 01 Kabupaten Brebes dalam pembelajaran IPA. Subjek dalam penelitian ini adalah siswa kelas IV SDN Sigempol 01 Kabupaten Brebes, dengan jumlah 28 anak yang terdiri dari 16 siswa laki-laki dan 12 siswa perempuan. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah tes, observasi dan dokumentasi. Instrumen penelitian menggunakan soal tes dan lembar observasi. Teknik analisis data menggunakan deskriptif kuantitatif dan kualitatif. Penelitian ini menggunakan Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, setiap siklus terdiri dari 2 pertemuan. Indikator yang ditetapkan antara lain; (1) minat belajar siswa pada Siklus 1 bahwa indikator nilai siswa kategori kurang 46% (13 siswa), nilai siswa kategori cukup 43% (12 siswa), nilai siswa kategori baik 11% (3 siswa). Meningkat pada siklus II dengan nilai siswa kategori kurang 21% (6 siswa), nilai siswa kategori cukup 61% (17 siswa), nilai siswa kategori baik 18% (5 siswa). (2) Hasil penelitian dapat disimpulkan antara lain hasil belajar siswa pada siklus I rata-rata kelas 63,9, persentase ketuntasan belajar klasikal 53,5%, dan meningkat pada siklus II rata-rata kelas mencapai 73,2 persentase ketuntasan klasikal belajar mencapai 83%. Disimpulkan bahwa adanya peningkatan pelajaran IPA materi perambatan bunyi melalui zat padat melalui media pembelajaran telepon mainan . Disarankan kepada guru untuk menerapkan media pembelajaran seperti telepon mainan dalam proses pelajaran IPA materi perambatan bunyi melalui zat padat.Dan dalam proses pembelajaran IPA hendaknya dikaitkan dengan kehidupan sehari-hari supaya materi akan mudah dipahami anak. Kata kunci: Minat, Hasil Belajar, Telepon mainan. EFFORTS TO INCREASE INTEREST AND LEARNING OUTCOMES OF SCIENCE SOUND PROPAGATION MATERIAL THROUGH SOLID SUBSTANCES WITH TOY TELEPHONE MEDIA IN GRADE IV STUDENTS OF SDN SIGEMPOL 01 SEMESTER 1 OF THE 2021/2022 ACADEMIC YEAR ABSTRACT Science learning for fourth grade students at SDN Siegempol 01 Brebes, Brebes Regency still uses the lecture method, students are less actively involved during the learning process and students find it difficult to relate science concepts to everyday life. This results in low student interest and learning outcomes. It can be seen from the results of the daily science tests on sound propagation through solids that some students scored below the specified KKM. The action taken to address this problem is the application of experimental teaching aids to understand the learning material. The aim is to find out and describe the interests and learning outcomes of class IV students at SDN Sigempol 01 Brebes Regency in learning science. The subjects in this research were fourth grade students at SDN Sigempol 01 Brebes Regency, with a total of 28 children consisting of 16 male students and 12 female students. The data collection techniques used in this research are tests, observation and documentation. The research instrument uses test questions and observation sheets. Data analysis techniques use quantitative and qualitative descriptive. This research uses Classroom Action Research (PTK) which is carried out in two cycles, each cycle consisting of 2 meetings. The indicators set include; (1) Student interest in learning in Cycle 1 is that the student score indicator in the poor category is 46% (13 students), the score in the sufficient category is 43% (12 students), the score in the good category is 11% (3 students). It increased in cycle II with students' scores in the poor category being 21% (6 students), students' scores in the sufficient category being 61% (17 students), and students' scores in the good category being 18% (5 students). (2) The results of the research can be concluded, among others, that student learning outcomes in the first cycle averaged 63.9, the percentage of classical learning completeness was 53.5%, and increased in the second cycle the class average reached 73.2, the percentage of classical learning complete reached 83%. It was concluded that there was an increase in science lessons regarding the propagation of sound through solid substances through the learning medium of toy telephones. It is recommended for teachers to apply learning media such as toy telephones in the science lesson process, material on the propagation of sound through solid substances. And in the science learning process, it should be linked to everyday life so that the material will be easy for children to understand. Keywords: : Interests, Learning Results, Toy phones.